2011
DOI: 10.1016/j.cub.2011.08.029
|View full text |Cite
|
Sign up to set email alerts
|

MRI Magnetic Field Stimulates Rotational Sensors of the Brain

Abstract: SUMMARY Vertigo in and around MRI machines has been noted for years [1, 2]. Several mechanisms have been suggested to explain these sensations [3, 4], yet without direct, objective measures, the cause is unknown. We found that all healthy human subjects lying in the static magnetic field of an MRI machine develop a robust nystagmus. Patients lacking labyrinthine function do not. Here we use the pattern of eye movements as a measure of vestibular stimulation to show that the stimulation is static (continuous, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
294
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(315 citation statements)
references
References 24 publications
20
294
1
Order By: Relevance
“…Also, a study by Heinrich et al (2014), which reported dizziness among volunteers exposed to homogeneous SMF inside bores of MRI-scanners with different magnet strengths, was not discussed. This work has been supported by experimental studies that examined the effect of a strong SMF on vestibular responses in human subjects and found an effect on involuntary eye movements and vertigo, both of which were associated with the direction of the SMF in relation to the vestibular organ (Roberts et al, 2011;Mian et al, 2013;Ward et al, 2014). ICNIRP did report that "A meta-analysis of 5 studies published during 1992-2007 found the only neuropsychological effect relating to static magnetic field exposure to be visual impairment.…”
supporting
confidence: 49%
“…Also, a study by Heinrich et al (2014), which reported dizziness among volunteers exposed to homogeneous SMF inside bores of MRI-scanners with different magnet strengths, was not discussed. This work has been supported by experimental studies that examined the effect of a strong SMF on vestibular responses in human subjects and found an effect on involuntary eye movements and vertigo, both of which were associated with the direction of the SMF in relation to the vestibular organ (Roberts et al, 2011;Mian et al, 2013;Ward et al, 2014). ICNIRP did report that "A meta-analysis of 5 studies published during 1992-2007 found the only neuropsychological effect relating to static magnetic field exposure to be visual impairment.…”
supporting
confidence: 49%
“…Roberts et al [10] demonstrated that horizontal slow-phase eye nystagmus velocity (H-SPV) produced by exposure to a strong magnetic field is directly proportional to the magnetic field strength, with a response which has an adaption component and a linear response to field. This linear response measurement provided a new and vital piece of objective evidence.…”
Section: Magneto-hydrodynamic Effect (Mhd)mentioning
confidence: 99%
“…Antunes et al [11]refined the calculation by Roberts et al by modelling the canals, currents and forces and confirmed that this mechanism is plausible and gives a realistic prediction of both the magnitude and direction of perception. As the Lorentz force is dependent on magnitude and directions of both magnetic field and orientation of the cupula then the SPV response is highly directional with both peaks and nulls in the response dependent upon head orientation [10,12]. The dynamics of the response may be modelled in terms of a low pass and high pass (partial) adaption model.…”
Section: Magneto-hydrodynamic Effect (Mhd)mentioning
confidence: 99%
See 2 more Smart Citations